Literasi Keuangan Digital dan Literasi Digital pada Manajemen Keuangan Usaha Perempuan - Bambang Santoso; Safrudin Safrudin; Atik Budi Paryanti; Amiruddin Amiruddin (Universitas Negeri Makassar, 2026)
Digital transformation has encouraged business actors to adopt various digital financial services in managing their business activities. However, effective financial management depends not only on general digital literacy but also on digital financial literacy, which reflects the ability to utilize digital financial technologies for financial decision-making. This study aims to examine the effects of Digital Financial Literacy and Digital Literacy on the Financial Management of women-owned household businesses in East Jakarta. A quantitative approach was employed using a survey of 114 women entrepreneurs selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that Digital Financial Literacy has a positive and significant effect on Financial Management (β = 0.413; p = 0.001), whereas Digital Literacy has a positive but insignificant effect (β = 0.148; p = 0.241). The coefficient of determination (R² = 0.287) indicates that both variables explain 28.7% of the variance in Financial Management. These findings suggest that the ability to utilize digital financial services plays a more important role in improving financial management than general digital literacy. Therefore, programs aimed at empowering women entrepreneurs should prioritize strengthening digital financial literacy to enhance the quality of business financial management